Design, development and experimental validation of dual output stator-less motor - MUSHTAQ, SHAHRYAR (2018)
This thesis is about the experimental studies of a mechanism consisting of two concentric rotors that can be converted into a dual-output stator-less motor. Whereas the conventional motors consist of at least one stator and rotary part. This novel concept consists of only rotors with no stators installed. In this proposed mechanism the rotors are meshed into each other, wherein the blade of the first rotor comprises of electromagnets while the blade of the second rotor comprises of permanent magnets. Each rotor is connected to its own shaft installed with an overrunning clutch which allows both rotors to rotate only in a single direction.